Conditional symmetry and reduction of differential equations with partial derivatives - Fushchich , W. I.; Zhdanov , R. Z. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We establish sufficient conditions of reduction of partial differential equations admitting nontrivial conditional symmetry. The results obtained generalize the classical conditions of reduction of differential equations by using group-invariant solutions. Some examples of reduction of systems of partial differential equations both by number of independent and dependent variables are considered.